BILATERAL AGENESIS OF THE HUMAN INTERNAL CAROTID ARTERY - A. Usovich; L. Davydova; A. Kotovich; K. Usovich; A. Kalinina (Trakia Journal of Sciences)
Anomalies of the internal carotid artery associated with a violation of its embryonic development are classified as follows: agenesis, aplasia and hypoplasia. Agenesis is a rare vascular abnormality. The search and analyze the scientific articles data concerning the ICA embryogenesis and agenesis, absence of the internal carotid artery, to make comparative analysis of the adult skull with and without ICA. 104 human skulls served us as the research material.